Buffer regulation of calcium puff sequences - Fraiman Borrazás, Daniel Edmundo (2014)
Puffs are localized Ca2 + signals that arise in oocytes in response to inositol 1,4,5-trisphosphate (IP3). They are the result of the liberation of Ca2 + from the endoplasmic reticulum through the coordinated opening of IP3 receptor/channels clustered at a functional release site. The presence of buffers that trap Ca2 + provides a mechanism that enriches the spatio–temporal dynamics of cytosolic calcium. The expression of different types of buffers along the cell's life provides a tool with which Ca2 + signals and their responses can be modulated. In this paper we extend the stochastic model of a cluster of IP3R-Ca2 + channels introduced previously to elucidate the effect of buffers on sequences of puffs at the same release site. We obtain analytically the probability laws of the interpuff time and of the number of channels that participate of the puffs. Furthermore, we show that under typical experimental conditions the effect of buffers can be accounted for in terms of a simple inhibiting function. Hence, by exploring different inhibiting functions we are able to study the effect of a variety of buffers on the puff size and interpuff time distributions. We find the somewhat counter-intuitive result that the addition of a fast Ca2 + buffer can increase the average number of channels that participate of a puff.